(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2023)
The pre-Roman Greek inscriptions found in the Iberian Peninsula are a valuable testimony for several aspects of the contact between Greeks and Iberians, and the possible influence of the Greek epigraphic habit in the Iberian one, but also to provide possible parallels and ways of interpretation in the study of the Iberian inscriptions.